Social Learning and Distracted Driving among Young Adults - Tontodonato, Pamela (American journal of criminal justice, 2020)
This paper examines the relevance of Akers’ social learning theory (Akers and Jensen 2006 ; Akers and Jennings 2009 ) for the problem of distracted driving. Distracted driving is widespread and dangerous, with many drivers, particularly youthful ones, continuing to engage in such driving despite knowledge of its risks (see, e.g., Atchley et al. 2011 ; Prat et al. 2017 ). Much of the research to date is limited to texting; however, in recent years, cell phones have become major tools for entertainment and information, especially among younger people, resulting in the emergence of newer forms of distracted driving. Explanations of distracted driving from a criminological approach are limited (Quisenberry 2015 is an exception), yet criminological theory can contribute to our understanding of this relatively new and expanding form of deviance. Drawing on social learning theory, we explore the attitudes and behaviors of 935 college students regarding ‘traditional’ and newer types of phone-related distracted driving, as well as their perceptions of self and others’ cell phone use. Multivariate analysis indicates support for some of the social learning concepts, with definitions and one of the differentialreinforcement measures standing out in particular (perceived benefits of cell phone use while driving). We consider the implications of these findings for theory and policy.